Current and advancing systemic treatment options for soft tissue sarcomas. (September 2015) - Harris, Samuel J; Benson, Charlotte; Jones, Robin L
Abstract : Introduction: Soft tissue sarcomas are a collection of rare malignancies, the treatment of which has evolved over time. Although cytotoxic chemotherapy remains the cornerstone of management of metastatic disease, many new treatments have been developed or show great promise in the treatment of soft tissue sarcoma. Research into the different underlying pathogenesis of individual subtypes has driven progress in treatment. This has allowed development of treatments targeted to specific subtypes of sarcoma. Areas covered: We provide a review of the current field of systemic therapy in soft tissue sarcoma. This is followed by an in-depth analysis of recent developments in treatment, as well as new treatments that are aimed at specific subtypes of sarcoma, and the biological rationale behind these therapies. We also look in detail at the promising new agents currently in development. Expert opinion: Much progression has been made in treatment of soft tissue sarcomas with multiple exciting new treatments in development. However outcomes in general remain poor. Further research into the underlying pathogenesis of soft tissue sarcomas may help deliver more effective systemic therapies. Increased collaboration between basic science, translational and clinical investigators is required at national and international levels to maximise progress.